2002
DOI: 10.1099/00221287-148-5-1483
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of the psa genes from Streptococcus pneumoniae in multiple models of infection

Abstract: Differential fluorescence induction technology was used to identify promoters of Streptococcus pneumoniae genes that are expressed during lung infection of the mouse. Among the promoter clones that were identified multiple times was the psa promoter, which drives expression of the psaBCA operon. These genes have been identified previously and shown to encode a manganese permease system as well as play a role in the virulence of this organism. Mutations in psaB, psaC or psaA result in growth limitation in low m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 35 publications
4
120
1
1
Order By: Relevance
“…A previous study from our group showed that the high affinity manganese transporter, SsaB, is essential for O 2 tolerance and endocarditis virulence in S. sanguinis (26). This mirrored earlier findings showing that orthologs of this transporter are essential for endocarditis caused by other oral streptococci (29,30) for pneumonia, bacteremia, and otitis media caused by Streptococcus pneumoniae (31)(32)(33)(34), for bacteremia caused by S. pyogenes (35), and for mastitis caused by Streptococcus uberis (36). It is known that Mn II contributes to O 2 tolerance in part by serving as a cofactor for the superoxide dismutase SodA.…”
Section: Discussionsupporting
confidence: 75%
“…A previous study from our group showed that the high affinity manganese transporter, SsaB, is essential for O 2 tolerance and endocarditis virulence in S. sanguinis (26). This mirrored earlier findings showing that orthologs of this transporter are essential for endocarditis caused by other oral streptococci (29,30) for pneumonia, bacteremia, and otitis media caused by Streptococcus pneumoniae (31)(32)(33)(34), for bacteremia caused by S. pyogenes (35), and for mastitis caused by Streptococcus uberis (36). It is known that Mn II contributes to O 2 tolerance in part by serving as a cofactor for the superoxide dismutase SodA.…”
Section: Discussionsupporting
confidence: 75%
“…In contrast to some Gram-negative pathogens, the virulence genes of S. pneumoniae are not generally clustered together. Wholegenome microarray analysis has depicted the differential expression of genes under invasive and non-invasive conditions, and cross-linking of the data with the results of STM and DIF screens provides an extended list of putative virulence factors Orihuela et al, 2004;Marra et al, 2002). These virulence factors can be regulated by one-component regulatory systems, including luxS, rlrA, regM/R and mgrA, or by one of the 14 TCSs that have been identified in S. pneumoniae (Hoskins et al, 2001;Tettelin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the finding that mucosal immunization of mice with PsaA is highly protective against pneumococcal carriage (Johnson et al, 2002). Differential fluorescence induction (DIF) analysis has demonstrated the upregulation of the psa promoter of the psaBCA operon during lung infections, and microarray analysis has demonstrated that psaA is upregulated during attachment of pneumococci to nasopharyngeal cells (Marra et al, 2002;Orihuela et al, 2004).…”
Section: Lipoproteins: Implications In Substrate Transport and Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…S. pneumoniae is a causative agent of bacterial pneumonia, meningitis, septicaemia and otitis media [5,6] and is the foremost bacterial pathogen associated with mortality in children less than 5 years old worldwide [7]. Manganese has crucial roles in S.…”
Section: Introductionmentioning
confidence: 99%